Morphology of spines and milking practices in venomous fishes - Giovanni Annona; Andrea Tarallo; Lisa Locatello; Pasquale De Luca; Maria Vittoria Modica (Discover Animals)
Abstract Venomous fish have independently evolved venom-delivery systems multiple times throughout their evolution. Despite the remarkable convergence of such structures, a large variety in venom-delivery structures morphology does occur across species. This review is aimed at surveying fish species’ peculiarities, exploring the diversity of their venom glands and the potential ecological roles in relation to habitats and associated food webs. A detailed knowledge of the anatomy of highly diverse venom systems is a fundamental prerequisite to developing new and effective approaches to venom collection from different fish species. Here, we discuss the venom collection and stabilization techniques in light of this morphological diversity. Current extraction methods include the crushing of venomous structures, the direct extraction from glands, and pressure-based milking techniques, and the effectiveness of each technique varies depending on the species. The recent advances in venom extraction techniques, here presented, offer new perspectives not only for biotechnological applications but also to deepen into venom’s broader ecological and evolutionary roles. Our review, by providing an extensive comparative characterization of the venom delivery systems in relation to fish ecology, highlights gaps that remain to be addressed to promote multiple research areas and potential applicative developments.